GUIDELINES FOR DEVELOPING INTEGRATED LEARNING MANAGEMENT UNDER NAKHON PHANOM PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Srisuthum, Ratchanee; Udorn, Nawee; Hanrin, Chanwit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purposes of this research were to 1) examine the current and desirable conditions of integrated learning management, 2) assess the needs for developing integrated learning management, 3) develop guidelines for integrated learning management, and 4) evaluate the guidelines for developing integrated learning management under Nakhon Phanom Primary Educational Service Area Office 1. The sample, obtained through multi–stage sampling, included 28 school administrators and 211 teachers during the academic year 2023, totaling 239 participants. The percentage criteria were also used in determining the sample size. The statistics employed were mean, standard deviation (S.D.), and the modified priority needs index (PNI Modified). The results revealed that: 1) The current conditions of integrated learning management were overall at a high level, while the desirable conditions were overall at the highest level; 2) The needs for developing integrated learning management were higher than the overall values, covering two aspects: Integrated Instruction in the Classroom, and Intradisciplinary Integration; and 3) The guidelines for developing integrated learning management were rated overall at a high level, with the highest level of suitability, and a high level of feasibilities.